2009
DOI: 10.1097/jto.0b013e3181a94a2f
|View full text |Cite
|
Sign up to set email alerts
|

Response Rate Is Associated with Prolonged Survival in Patients with Advanced Non-small Cell Lung Cancer Treated with Gefitinib or Erlotinib

Abstract: We found a significant relationship between RR and MST in clinical trials with EGFR-TKIs. RR could be an independent surrogate marker for MST in the current response criteria in the clinical trials of EGFR-TKIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 41 publications
1
20
2
Order By: Relevance
“…Our results do not correspond with some previous results that have indicated that tumor response and PFS are surrogate endpoints for OS in advanced NSCLC [24,25]. We analyzed our results pertaining to first-line therapy, and they suggested that PFS and tumor response did not adequately reflect OS in such settings.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results do not correspond with some previous results that have indicated that tumor response and PFS are surrogate endpoints for OS in advanced NSCLC [24,25]. We analyzed our results pertaining to first-line therapy, and they suggested that PFS and tumor response did not adequately reflect OS in such settings.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results do not correspond to those of certain previous studies indicating that tumor response and PFS may be surrogate endpoints for OS in advanced NSCLC (24,25). In our patients with advanced NSCLC harboring EGFR mutations who received first-line gefitinib, PFS and tumor response did not reflect OS.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, our results also showed deletions in exon 19 occurring at different amino acid positions were associated with different RR. In patients with advanced NSCLC under EGFR TKIs, the RR to EGFR TKIs correlate with the length of median PFS (29). However, at least 14% increase of RR was needed to prolong median PFS by 1 month.…”
Section: Discussionmentioning
confidence: 99%